PENERIMAAN DIRI BAGI PENYANDANG DISABILITAS NETRA - RAHMAH, RAHMAH (Alhadharah: Jurnal Ilmu Dakwah, 2019)
People with visual disabilities are someone who has a sense of vision (both) do not function as channels of information in their activities as normal people. This means that a blind person has a disability in the sense of vision so that the vision function is not the same as people in general. Disabilities in persons with visual impairments have a major influence on daily life.The physical limitations of people with visual impairments hamper any activities that are normally carried out by normal (seeing) people. These limitations affect the mental condition of persons with blind disabilities, for example a feeling of inferiority towards the physical possessed, then fear and insecurity about their potential, this is a problem that must be faced by persons with blind disabilities.Persons with disabilities who are blind with imperfections of their sense of sight will naturally experience various problems including those related to their self-acceptance, because it is not easy for those with disabilities to be able to accept themselves, and will require a long time, until it is embedded in him that experiencing blindness is not the end of everything, and with limitations on their sense of sight they still have a strong desire and determination to realize their desires, and are able to adapt themselves to their circumstances and environment by seeing themselves as they really are and recognizing themselves as they really are.Persons with visual impairments, whether innate or not, who have self-acceptance they will have the confidence to face problems, have the same degree as others, can receive praise, be able to accept criticism, able to accept limitations and strengths that exist in themselves, have a positive assessment of himself, able to control his emotional state, and be responsible